Percepción de los Comerciantes de autopartes sobre el Régimen Simple De Tributación en el Municipio De Duitama (2022)
The simple tax regime was created with the purpose of achieving greater collection for the National State but also as an instrument to reactivate the economy, encourage the generation of formal employment, unify several taxes in a single form, likewise, it offers a series of benefits that at first sight it is attractive to move to this, since it reduces tax rates, simplifies the management of costs and expenses and seeks to improve the taxpayer's cash flow, in this way they can undertake new projects or simply maintain their business. The main objective of the research is to identify the causes that lead traders who develop commercial activities of parts, parts and accessories for motor vehicles in the municipality of Duitama to be taxed in the simple regime, created through Article 66 of the Financing Law 1943 of 2018, declared unenforceable by the Constitutional Court, but finally ratified by Article 74 of the Economic Growth Law 2010 of 2019; one of the bets of the National Government to bring formality to Colombians.